Penyuluhan dan Pelatihan Pengolahan Limbah Plastik Menjadi Bahan Bakar Minyak Untuk Mengatasi Sampah Plastik Di Kota Bontang - Ahmad Yani; Irhamni Nuhardin; Mimin Septiani; Fitria Fitria; Irianto Irianto; Ratnawati Ratnawati (Sekolah Tinggi Teknologi Industri (STTI) Bontang, 2021)
Plastic waste is a type of inorganic waste that is difficult to decompose in soil and water. Plastic waste is usually only piled up and disposed of, causing various kinds of negative impacts. One of the efforts to tackle plastic waste in Bontang City is to create a tool that can convert plastic waste into fuel oil. The purpose of this community service is to provide an understanding to the community (students) regarding the dangers of plastic waste to the environment and to provide knowledge to the public about how to process plastic waste into fuel oil using practical and inexpensive pyrolysis technology. The method of implementing this community service activity is in the form of counseling and training. The results of this community service received a very good response from students and teachers. This response can be seen from the enthusiasm of the participants when carrying out the practice of processing plastic waste into fuel oil. The conclusion of this community service has a very positive impact on the processing of plastic waste into fuel oil and changes the habits of the Bontang people, which initially only disposed of plastic waste, then utilized it so that it had economic value.